Glutathione reductase-catalyzed cascade of redox reactions to bioactivate potent antimalarial 1,4-naphthoquinones: a new strategy to combat malarial parasites - Müller, Tobias; Johann, Laure; Jannack, Beate; Brückner, Margit; Lanfranchi, Don Antoine; Bauer, Holger; Sanchez, Cecilia P.; Yardley, Vanessa; Deregnaucourt, Christiane; Schrével, Joseph; Lanzer, Michael; Schirmer, Rolf Heiner; et al. (Journal of the American Chemical Society, 2011)
Our work on targeting redox equilibria of malarial parasites propagating in red blood cells has led to the selection of six 1,4-naphthoquinones, which are active at nanomolar concentrations against the human pathogen Plasmodium falciparum in culture and against Plasmodium berghei in infected mice. With respect to safety, the compounds do not trigger hemolysis or other signs of toxicity in mice. Concerning the antimalarial mode of action, we propose that the lead benzyl naphthoquinones are initially oxidized at the benzylic chain to benzoyl naphthoquinones in a heme-catalyzed reaction within the digestive acidic vesicles of the parasite. The major putative benzoyl metabolites were then found to function as redox cyclers: (i) in their oxidized form, the benzoyl metabolites are reduced by NADPH in glutathione reductase-catalyzed reactions within the cytosols of infected red blood cells; (ii) in their reduced forms, these benzoyl metabolites can convert methemoglobin, the major nutrient of the parasite, to indigestible hemoglobin. Studies on a fluorinated suicide-substrate indicate as well that the glutathione reductase-catalyzed bioactivation of naphthoquinones is essential for the observed antimalarial activity. In conclusion, the antimalarial naphthoquinones are suggested to perturb the major redox equilibria of the targeted infected red blood cells, which might be removed by macrophages. This results in development arrest and death of the malaria parasite at the trophozoite stage.
Gesehen am14.09.2022